Generic Structure and Cohesive Devices: A Study on the Final Project Report Presentation of the Accounting Students of Polines Semarang - Raharjo, Suko; Nirmala, Deli (PAROLE: Journal of Linguistics and Education, 2016)
This study examines the generic structure and cohesive devices in the Final Project Report (FPR) presentation delivered in English by the Accounting students of Polines. Fourteen randomly selected subjects (10% of the third graders’ population) were involved and audio-recorded during their presentation. The recordings were then transcribed and analyzed using a descriptive-interpretative method. The result shows that the generic structure most presenters used was Greeting and Salutation–Self Introduction–Topic Introduction–Body–Summary–Conclusion, in which the Body mostly consists of Background or Object of the Study, Problem Statement, Aims of the Study, Research Method, and Results and Discussion, and the Summary consists of Conclusion and Suggestion. The major cohesive devices employed were conjunctives of Textual, hypotactic and paratactic types, referents of exophoric and anaphoric types, and repetition as part of lexical cohesion. The transition of stages was marked mostly with referents and specific lexical items. This study may contribute to teaching public speaking of the university students especially in presentation.